Vascularization in skin wound healing: where do we stand and where do we go? - Moreira, Helena Rocha (2022)
Cutaneous healing is a highly complex process that, if altered due to, for example, impaired vascularization, results in chronic wounds or repaired neotissue of poor quality. Significant progress has been achieved in promoting neotissue vascularization during tissue repair/regeneration. In this review, we discuss the strategies that have been explored and how each one of them contributes to regulate vascularization in the context of cutaneous wound healing from two different perspectives â biomaterial-based and a cell-based approaches. Finally, we discuss the implications of these findings on the development of the â next generationâ approaches to target vascularization in wound healing highlighting the importance of going beyond its contribution to regulate vascularization and take into consideration the temporal features of the healing process and of different types of wounds.